Modulation of Monoaminergic Transporters by Choline-Containing Phospholipids in Rat Brain - Khosrow Tayebati, Seyed; Tomassoni, Daniele; Ejike Nwankwo, Innocent; Di Stefano, Antonio; Sozio, Piera; Serafina Cerasa, Laura; Amenta, Francesco (CNS & Neurological Disorders - Drug Targets, 2013)
Choline-containing phospholipids were proposed as cognition enhancing agents, but evidence on their activity is controversial. CDP-choline (cytidine-5´-diphosphocholine, CDP) and choline alphoscerate (L-alpha-glycerylphosphorylcholine, GPC) represent the choline-containing phospholipids with larger clinical evidence in the treatment of sequelae of cerebrovascular accidents and of cognitive disorders. These compounds which display mainly a cholinergic profile interfere with phospholipids biosynthesis, brain metabolism and neurotransmitter systems. Dated preclinical studies and clinical evidence suggested that CDP-choline may have also a monoaminergic profile. The present study was designed to assess the influence of treatment for 7 days with choline-equivalent doses (CDP-choline: 325 mg/Kg/day; GPC: 150 mg/Kg/day) of these compounds on brain dopamine (DA), and serotonin (5-HT) levels and on DA plasma membrane transporter (DAT), vesicular monoamine transporters (VMAT1 and VMAT2), serotonin transporter (SERT), and norepinephrine transporter (NET) in the rat. Frontal cortex, striatum and cerebellum were investigated by HPLC with electrochemical detection, immunohistochemistry, Western blot analysis and ELISA techniques. CDP-choline did not affect DA levels, which increased after GPC administration in frontal cortex and cerebellum. GPC increased also 5-HT levels in frontal cortex and striatum. DAT was stimulated in frontal cortex and cerebellum by both CDP and GPC, whereas VMAT2, SERT, NET were unaffected. VMAT1 was not detectable. The above data indicate that CDP-choline and GPC possess a monoaminergic profile and interfere to some extent with brain monoamine transporters. This activity on a relevant drug target, good tolerability and safety of CDP-choline and GPC suggests that these compounds may merit further investigations in appropriate clinical settings.
Keywords: cerebral areas